Maternal effects and urbanization: Variation of yolk androgens and immunoglobulin in city and forest blackbirds. Issue 4 (4th February 2020) - Partecke, Jesko; Hegyi, Gergely; Fitze, Patrick S.; Gasparini, Julien; Schwabl, Hubert
Abstract: Wildlife inhabiting urban environments exhibit drastic changes in morphology, physiology, and behavior. It has often been argued that these phenotypic responses could be the result of micro‐evolutionary changes following the urbanization process. However, other mechanisms such as phenotypic plasticity, maternal effects, and developmental plasticity could be involved as well. To address maternal effects as potential mechanisms, we compared maternal hormone and antibody concentrations in eggs between city and forest populations of European blackbirds ( Turdus merula ), a widely distributed species for which previous research demonstrated differences in behavioral and physiological traits. We measured egg and yolk mass, yolk concentrations of androgens (androstenedione [A4 ], testosterone [T], 5α‐dihydrotestosterone [5α‐DHT], and immunoglobulins [IgY]) and related them to population, clutch size, laying order, embryo sex, and progress of breeding season. We show (a) earlier onset of laying in the city than forest population, but similar egg and clutch size; (b) higher overall yolk androgen concentrations in the forest than the city population (sex‐dependent for T); (c) greater among‐female variation of yolk T and 5α‐DHT concentrations in the forest than city population, but similar within‐clutch variation; (d) similar IgY concentrations with a seasonal decline in both populations; and (e) population‐specific positive (city) or negative (forest) association of yolk A4 and T with IgY concentrations. Our results are consistent with the hypotheses that hormone‐mediated maternal effects contribute to differences in behavioral and physiological traits between city and forest individuals and that yolk androgen and immunoglobulin levels can exhibit population‐specific relationships rather than trade‐off against each other. Abstract : Urbanization of animals is often associated with phenotypic alterations. These alterations are mainly discussed in the framework of adaptation or phenotypic plasticity. Maternal effects have been neglected so far. Our study highlights for the first time the potential of maternal effects in the urbanization process of animals.